Employment polarization and immigrant employment opportunities - Hanna Wielandt (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
Building on the task-based approach of technological change, this paper discusses the interaction between occupational polarization (e.g. a gradual increase of native employment in the lowest and highest-paying jobs) and employment opportunities of immigrant workers. Using high quality administrative data for Germany, I first show that technological change is positively related to employment growth of natives in low-paying occupations that are also typically held by immigrant workers. In a second step, I show that labor markets in which native employment in those low-paying occupations grew more also experienced a larger decline in immigrant employment rates. The findings are consistent with the idea that the reallocation of natives towards low paying occupations induces stronger competition in the low-skill labor market, a segment in which foreign workers are typically employed. The results suggest that this relationship is more relevant for recent immigrants who have been in Germany for less than 5 years, and that approximately one third of the decline in employment rates could be associated with occupational polarization of native employment.
Keywords: J24; J31; J62; O33; R23; 330; Job Tasks; Polarization; Technological Change; Immigration